SKRINING KESEHATAN PADA MASYARAKAT SEBAGAI UPAYA PENCEGAHAN PENYAKIT TIDAK MENULAR - Idayani, Sri; Tandea, Gisel Audina; Adnyani, Widya (Universitas Islam Malang, 2024)
Non-Communicable Diseases (NCDs) are diseases that are not caused by infection with microorganisms such as protozoa, bacteria, fungi or viruses. The aim of this activity is to improve the quality of health and knowledge about health and controlling Non-Communicable Diseases (NCDs). This method of implementing community service is carried out using approaches and outreach to partners, education, training and evaluation. providing education in the form of counseling about Non-Communicable Diseases (PTM), namely blood sugar and uric acid as well as health screening for blood sugar and uric acid. The stages that have been implemented in this activity have had a positive impact on the knowledge and quality of health of the elderly. This has an important role in providing information for preventing non-communicable diseases (NCDs), blood sugar and gout. The results of counseling and screening show that the knowledge of the elderly has increased in the sufficient category and the quality of health based on health screening, blood sugar and uric acid examinations is mostly in the normal category. So based on the data above, health education and screening activities are effective in improving the knowledge and quality of health of the elderly.